Novel Method and Device for Fully Non-Invasive Cerebrovascular Autoregulation Monitoring - Petkus, V.; Preiksaitis, A.; Krakauskaite, S.; Chomskis, R.; Rocka, S.; Kalasauskiene, A.; Kalvaitis, E.; Ragauskas, A. (Elektronika ir Elektrotechnika, 2014)
The novel method and the device for non - invasive cerebrovascular autoregulation (CA) status monitoring without using the arterial blood pressure (ABP) measurement channel are presented. This fully non-invasive CA monitor is based on the ultrasonic time-of-flight measurement of cerebral blood volume pulsations within the brain parenchyma, extraction of informative and reference slow and respiratory volumetric waves and calculation of CA estimating indexes without using any additional ABP measurements. For demonstrating the applicability of the proposed method, the CA status was monitored on 11 traumatic brain injury patients simultaneously by using the novel fully non-invasive monitor and compared to the CA status representing indexes calculated from the invasively measured intracranial pressure (ICP) and ABP slow waves. The total monitoring time was about 22 hrs. The correlation factor between the invasively and non-invasively obtained CA data showed significant agreement (r=0.751) between the two methods. The proposed innovative CA real-time monitoring method gives us new possibilities to perform estimation of the CA status from the intracranial waves only as well as to exclude the ABP line’s errors and artifacts from the measurement results. DOI: http://dx.doi.org/10.5755/j01.eee.20.8.5464